Uporabnost teorij etike v zdravstveni negi - Šmitek, Jana (Obzornik zdravstvene nege, 2004)
Two ethical theories are in more detail explained in the article: deontology as principle based ethics and ethics of care as a theory related to fundamental value of nursing caring. Joan Tronto's presentation of care and ethics of care is exposed as well as it's direct relation to nursing care. Theauthor exposes the need for ethics of care theory to be implemented into nursing educational programmes and also into educational programmes of other health care professionals.
Keywords: ethics; Ethics, Nursing; etika; Etika zdravstvene nege; medicinske sestre; Nursing Theory; zdravstvena nega; Zdravstvena nega, teorija